Karakterisasi Keragaan Agronomis Varietas Padi Sawah Tadah Hujan pada Pemupukan Nitrogen dan Perlakuan Air - Zaqiah M. Hikmah; Nurwulan Agustiani; Sriyana Sriyana; K. Hayashi (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2017)
Hikmah et al, 2017. Characterization of Agronomic Traits on Two Rainfed Rice Varieties on Several Levels of Nitrogen Fertilizers and Water Treatments. JLSO 6(2):176-184.Rainfed rice varieties are expected to increase yield on rainfed fields. This research aim was to identify various agronomic characters including yield of rainfed rice varieties. It was conducted at the Sukamandi Field Station at rainy season 2016/2017, using a split split plot design with 4 replications. Water management as the main plot with two levels (I1: irrigated and I2: rainfed). Nitrogen (N) fertilizer dosage as subplot with three levels (P1: 0 kg N/ha, P2: 60 kg N/ha, and P3: 120 kg N/ha) and varieties as subplots with two levels (V1: Inpari 39 Tadah Hujan Agritan and V2: Inpari 41 Tadah Hujan Agritan). The results showed that water treatment and N dosage on each variety gave different response on their agronomic characters, including yield. Tiller numbers per hill was strongly influenced by water management and dosage of N fertilizer. In irrigated treatment, tiller number increased linearly increasing N dosage. In rainfed,Inpari 41 Tadah Hujan Agritan reach maximum tiller number with 80 N kg/ha which more efficient than Inpari 39 Tadah Hujan Agritan with 91,97 N kg/ha. Rice yield was significant effected by N fertilizer and the genetic trait of each variety. The yield of Inpari 41 Tadah Hujan Agritan was higher than the Inpari 39 Tadah Hujan Agritan. Inpari 41 Tadah Hujan Agritan reached 5.70 t/ha GKG and Inpari 39 Tadah Hujan Agritan 4.62 t/ha.